Knowledge of the ovulatory cycle and its determinants among women of reproductive age in Papua New Guinea: Insights from a population-based study - McKenzie Maviso; Gracelyn Potjepat; Elias Namosha; Nancy Geregl; Paula Z. Aines; Lisa M. Vallely (PLoS ONE, 2025)
Background Correct knowledge of the ovulatory cycle is crucial for preventing unintended pregnancies and improving women’s reproductive health. However, the factors affecting this knowledge among women in Papua New Guinea (PNG) remain unclear. This study aimed to assess the prevalence and determine the factors influencing women’s knowledge of the ovulatory cycle in PNG. Methods Data from the PNG Demographic and Health Survey (DHS) was analyzed. Multivariable logistic regressions were used to determine factors associated with women’s knowledge of the ovulatory cycle. Adjusted odds ratios (aOR) with their 95% Confidence Intervals (CI) were reported. A p ≤ 0.05 was considered statistically significant. Results Of 12,580 women in this study sample, 22% (n = 2,773) had correct knowledge of the ovulatory cycle. Women from the Highlands region (aOR 1.31, 95% CI: 1.00–1.88) and the Momase region (aOR 1.56, 95% CI: 1.15–2.13), those who identified as Christians (aOR 3.01, 95% CI: 1.38–6.59), owned a mobile phone (aOR 1.29, 95% CI: 1.04–1.59), read a newspaper or magazine (aOR 1.30, 95% CI: 1.10–1.54), and had Internet access (aOR 1.21, 95% CI: 1.00–1.85) had higher odds of correct knowledge of the ovulatory cycle. Similarly, those who knew any contraceptive method (aOR 2.13, 95% CI: 1.58–2.87) and currently used the modern method (aOR 1.26, 95% CI: 1.02–1.56) or traditional/folkloric method (aOR 1.82, 95% CI: 1.36–2.43) were more likely to have correct knowledge of the ovulatory cycle. However, knowledge of the ovulatory cycle remained lower among women aged 15–24 and 25–34, those with lower education levels, and those from the Southern region. Conclusions In this study, less than a quarter of women had correct knowledge of the ovulatory cycle. Promoting reproductive health knowledge and awareness through educational curricula and mass media platforms could enhance women’s understanding of the ovulatory cycle, particularly among younger and less educated and empower them to make informed decisions about their reproductive health.